Current legal problems 2002 - Freeman, Michael D.A. (Oxford, UK : Oxford University Press, 2003)
Current Legal Problems, 55th volume, explores a range of subjects, both novel (legal memetics and the implications of immortality), and more conventional (the relationship between common law and equity, and the rule of law). There are essays on private and public international law, on European Community law, and on an'English' constitution.
Includes bibliographical references and index.
Keywords: Law -- England; Law -- Interpretation and construction -- England